Integration of Rahmatan Lil Alamin Student Profiles in the Madrasah Aliyah Curriculum - Siti Nurmela; Yanto Maulana Restu; Mada Sumringah Sari; Badrudin; Qiqi Yuliati Zaqiah (al-Afkar, Journal For Islamic Studies, 2025)
This study aims to describe the integration of the Rahmatan lil Alamin Student Profile into the Madrasah Aliyah curriculum. This type of research is a qualitative research with a library study method. Data sources in this study include primary data sources and secondary data sources from various reliable references such as scientific journals, books, and other sources that support the research. Data analysis in this study includes data collection, data presentation, data reduction, and drawing conclusions. The results of the study indicate that the integration of the Rahmatan lil Alamin Student Profile into the Madrasah Aliyah curriculum can be done through co-curricular, intracurricular, and extracurricular activities. The implementation model of the integration of the Rahmatan lil Alamin Student Profile into the Madrasah Aliyah curriculum is broadly divided into three, namely integration within one discipline or subject (within single disciplines), integration across several disciplines, and integration between and between (internal) learners (within and across learner). Factors that support and hinder the process of integrating the Rahmatan lil Alamin Student Profile values ​​into the Madrasah Aliyah curriculum are closely related to the understanding of educators, commitment and cooperation between the entire madrasah community, support for facilities and infrastructure, support and cooperation between educators and parents, and the diverse backgrounds of students.